(untitled) (Research, Society and Development, 2022)
The dentigerous cyst is the most common type of developmental cyst and the second in cysts affecting the jaws. It is a benign lesion in association with the odontogenic epithelium of the crown of an unerupted tooth, thus forming a cavity delimited by the reduced enamel epithelium filled with cystic fluid. It can be associated with any impacted tooth, however, it is more frequently found in lower third molars. The objective of the present study is to report a case of a 19-year-old normosistemic female patient who was referred to the Stomatology clinic at UFC- Sobral. Clinically, an increase in volume was observed in the region of teeth 25, 26, and 27. A panoramic radiographic examination was requested for analysis, in which a unilocular radiolucent area was observed in the region of the molars in the left maxilla. He also had teeth 18,28,38,37 and 48 included. In the region of the upper left molars, an incisional biopsy was performed followed by decompression. After the considerable reduction of the lesion, which resulted in a dentigerous cyst histopathologically, tooth 28 was extracted, and, subsequently, teeth 18 38, and 48 were removed. The cyst associated with tooth 48 caused external resorption of the distal root of 47, which showed vitality in the semiotechnical exams to detect pulp vitality and is undergoing clinical and radiographic follow-up. The patient resumed orthodontic treatment and a mini-implant was installed for the traction of tooth 37. Currently, the patient is at the end of orthodontic treatment without showing a recurrence of lesions associated with third molars.